Ciprofloxacin Does Not Exert Nephrotoxicity in Rats - Baykal, Asli (2005)
Ciprofloxacin, a member of the fluoroquinolone class, is an antibiotic used as a treatment for infections including the Anthrax bacteria. Studies concerning the safety and efficacy of ciprofloxacin have been controversial with respect to nephrotoxicity. Using rats orally treated with ciprofloxacin (400mg/kg/d), the effects of this drug were analyzed measuring several indications of nephrotoxicity: -NAG, creatinine, blood urea nitrogen, and sodium and potassium levels in blood samples. Additionally, histological analyses were performed. -NAG values, a measure of early renal damage, were significantly increased after 4 and 7 days of treatment (p = 0.001 and p = 0.004, respectively) compared with control rats. However, 7 days post-treatment, -NAG values decreased to control levels indicative that adaptive responses were induced to prevent nephrotoxicity. These results indicate that ciprofloxacin in doses comparable to those commonly prescribed does not induce nephrotoxicity. Altogether, they further support the idea that ciprofloxacin can be safely used